2018
DOI: 10.1111/aos.13886
|View full text |Cite
|
Sign up to set email alerts
|

Plasma markers of chronic low‐grade inflammation in polypoidal choroidal vasculopathy and neovascular age‐related macular degeneration

Abstract: Purpose: Ageing is the strongest predictor of neovascular age-related macular degeneration (AMD), where neuroinflammation is known to play a major role. Less is known about polypoidal choroidal vasculopathy (PCV), which is an important differential diagnosis to neovascular AMD. Here, we report plasma markers of inflammation with age (inflammaging) in patients with PCV, patients with neovascular AMD and a healthy age-matched control group. Methods: We isolated plasma from fresh venous blood obtained from partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 65 publications
(98 reference statements)
1
47
0
Order By: Relevance
“…However, CCR5 is expressed on monocytes during inflammation, and CCR5+ monocytes play a crucial role in orchestrating an appropriate sepsis immune response. 34 In this study, CCR5 expression on monocytes is slightly increased in patients with late-stage AMD, which is in line with the association between both late stages of AMD and systemic low-grade chronic inflammation, with the highest levels in patients with GA. 20,23 Plasma levels of CCL5 increases as a function of age and "inflammaging," 35 therefore it is not surprising to find this chemokine increased in aged individuals and in patients with GA, whom we have previously found to have accelerated immunological aging and chronic inflammation. 20 Rentzos et al 36 reports a similar increase in plasma CCL5 in patients with Parkinson disease.…”
Section: Discussionmentioning
confidence: 96%
“…However, CCR5 is expressed on monocytes during inflammation, and CCR5+ monocytes play a crucial role in orchestrating an appropriate sepsis immune response. 34 In this study, CCR5 expression on monocytes is slightly increased in patients with late-stage AMD, which is in line with the association between both late stages of AMD and systemic low-grade chronic inflammation, with the highest levels in patients with GA. 20,23 Plasma levels of CCL5 increases as a function of age and "inflammaging," 35 therefore it is not surprising to find this chemokine increased in aged individuals and in patients with GA, whom we have previously found to have accelerated immunological aging and chronic inflammation. 20 Rentzos et al 36 reports a similar increase in plasma CCL5 in patients with Parkinson disease.…”
Section: Discussionmentioning
confidence: 96%
“…As a characteristic in common, the elevated concentration of circulating CPR may partially explain the association between insomnia and incident AMD risk. Besides, increased circulating level of interleukin-6, an upstream inflammatory biomarker, has also been reported in patients with AMD (Haas et al 2015;Subhi et al 2019) and midlife women with low sleep efficiency (Nowakowski et al 2018).…”
Section: Discussionmentioning
confidence: 97%
“…Although no studies have reported a higher NLR in patients with polypoidal choroidal vasculopathy, studies have found immunological differences between neovascular AMD and polypoidal choroidal vasculopathy (Subhi et al. ,b, ,b), so this is an important factor potentially influencing the summary measures. Finally, this review is based on findings from six studies with 777 patients and 401 controls, which on the one hand is sufficient to give some basic insight, but on the other hand can also be considered limited in size and more studies are needed to give more detailed and conclusive insight into the matter.…”
Section: Discussionmentioning
confidence: 99%
“…; Subhi et al. ,b, ,b) which seem to play a complex intertwined role. Recent studies demonstrate that specific clinical features may be linked to specific immunological phenotypes in the systemic immunity (Singh et al.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation